Security of mobile money transfer in telecommunication industry in Tanzania, - Mikumuo, Shamte (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Masters of Science in Marketing Management (MSc-MKT) of Mzumbe University.